Lunch Break Activity impact on Afternoon Productivity in Mahindra and Mahindra Ltd. in Nagpur. - Ashok Tikhade, Nikita; B. Tekade, Atul B. Tekade (Journal of Neonatal Surgery, 2025)
Lunch break activities significantly influence employee productivity during post-lunch hours, particularly in high-performance environments. This study explores the correlation between various lunch break practices and their subsequent impact on afternoon productivity at Mahindra and Mahindra Ltd. in Nagpur. A mixed-methods approach was adopted, combining quantitative productivity metrics and qualitative employee feedback to provide a comprehensive analysis. Key findings reveal that engaging in recreational or mindfulness activities during lunch breaks leads to enhanced focus, reduced fatigue, and higher efficiency levels in the afternoon. Conversely, unstructured breaks or excessive screen time were observed to correlate with diminished performance and increased lethargy. The research also emphasizes the role of workplace culture in promoting effective break utilization, highlighting how structured wellness programs and ergonomic policies can further optimize employee performance. By identifying specific practices that drive productivity, this study provides actionable insights for organizations seeking to balance employee well-being with operational efficiency.